Chelsea shows her work in finding the solution to 4x−5=2+3(x−3). After checking her answer in the original equation, she found that it did not work. Where did she make a mistake?

Chelsea shows her work in finding the solution to 4x523x3 After checking her answer in the original equation she found that it did not work Where did she make a class=

Respuesta :

quita los paréntesis: 4x-5=2+3(x-3) multiplica paréntesis X3, elimina el paréntesis: 4x-5=2+3x-9 calcule: 4x-5= -7+3x mueve los términos y te quedará así: 4x-3x-5=-7

agrupe los términos semejantes: x=-7+5

calcular la suma, y el resultado final sería: x= -2

Step-by-step explanation:

espero te sirva

Answer:

Step 4

Step-by-step explanation:

ACCESS MORE